The Association Between Elevated Estimated Glomerular Filtration Rate and Poor Clinical Outcomes of Pediatric Patients with Community-Acquired Bacterial Meningitis Receiving Vancomycin: A Ten-Year Retrospective Cohort Study - Cuiyao He; Yuhua Deng; Tingsong Li; Dongmei Deng; Fengjun Lv; Yuan Qu; Li Jiang; Siqi Hong; Xiaogang Hu; Yuanyuan Luo (Infectious Diseases and Therapy)
Abstract Introduction This study aimed to explore the association between elevated estimated glomerular filtration rate (eGFR) and poor prognosis in pediatric patients with community-acquired bacterial meningitis (BM) receiving vancomycin. Methods This retrospective cohort study included children aged 1 month to 18 years with community-acquired BM admitted to the Department of Neurology, Children’s Hospital of Chongqing Medical University (CHCMU) from 2013 to 2023. Relevant information for all patients was collected, and clinical outcomes were assessed using the Glasgow Outcome Scale (GOS) at the time of discharge. Logistic regression analysis, receiver operating characteristic (ROC) curve analysis, integrated discrimination improvement (IDI), net reclassification improvement (NRI) indices, and survival curve analysis were employed to investigate the associations between elevated eGFR and poor clinical outcomes in pediatric patients with community-acquired BM. Results A total of 119 patients were included. Significant differences in the eGFR were observed among pediatric patients with different prognoses (P < 0.05). The initial vancomycin trough concentration in the elevated eGFR group was significantly lower than that in the normal eGFR group [5.600 (4.590; 8.060) mg/L vs. 9.205 (7.500; 12.070) mg/L]. At discharge, the GOS scores of the two groups also significantly differed (P < 0.05). In the analysis of factors influencing poor prognosis in pediatric patients with BM, an eGFR ≥ 169.21 mL/min/1.73 m2 was identified as an important factor associated with poor clinical outcomes in both univariate and multivariate analyses. Incorporating the elevated eGFR factor into the predictive model significantly improved its diagnostic performance (NRI 0.624, P = 0.00297; IDI 0.1057, P = 0.00414). Kaplan‒Meier survival analysis also revealed that an eGFR ≥ 169.21 mL/min/1.73 m2 was associated with a greater likelihood of poor outcomes (P = 0.0092). Conclusion Elevated eGFR is associated with an increased risk of poor clinical outcomes in community-acquired BM in children.